2023
DOI: 10.1371/journal.pone.0285374
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent screen time and unhealthy food consumption in the context of the digital development in New Caledonia

Abstract: Objective For several years, the Pacific Island Countries and Territories (PICTs) have been undergoing digital developments that have had an impact on the time adolescents spend in front of screens. The association between screen time and the overconsumption of unhealthy foods has been observed but little studied in New Caledonia. The twofold aim of this research was to analyze adolescent screen time based on the number of screens at home, gender, place of living, ethnic community and family socio-professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…We note that, in our population of interest, there is an association between place of living and SES. Indeed, many rural adolescents are in the low SES category (Nedjar‐Guerre et al, 2023). However, the multinomial analysis included all the sociocultural factors and showed that place of living was a factor surpassing SES in explaining the discrepancies in sleep components, especially onset sleep time.…”
Section: Discussionmentioning
confidence: 99%
“…We note that, in our population of interest, there is an association between place of living and SES. Indeed, many rural adolescents are in the low SES category (Nedjar‐Guerre et al, 2023). However, the multinomial analysis included all the sociocultural factors and showed that place of living was a factor surpassing SES in explaining the discrepancies in sleep components, especially onset sleep time.…”
Section: Discussionmentioning
confidence: 99%